2020
DOI: 10.1111/hsc.13062
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, severity and experience of food insecurity in Australia: An investigation of food aid use

Abstract: High costs of living, low wage growth, and insufficient welfare payments have resulted in an increase in the number of Australians experiencing food insecurity. Much of the response to food insecurity in Australia occurs through informal food aid provided by charitable organisations. Australia, like Canada, the United Kingdom and other high-income countries, relies on a private, non-government, food assistance sector that is supported by philanthropy, food industry, and government donations (Lindberg, Whelan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…Food insecurity (a lack of access to safe, sufficient, and appropriate food [ 2 ]) is a complex social problem that is represented and understood in different ways [ 3 , 4 ]. Previously represented as a problem of individual or community responsibility that deflects from the need for government intervention [ 1 , 4 ], the determinants of food insecurity are increasingly understood to result from inadequate social protection, low wage growth, a lack of wage-setting policies, unemployment, and homelessness [ 1 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity (a lack of access to safe, sufficient, and appropriate food [ 2 ]) is a complex social problem that is represented and understood in different ways [ 3 , 4 ]. Previously represented as a problem of individual or community responsibility that deflects from the need for government intervention [ 1 , 4 ], the determinants of food insecurity are increasingly understood to result from inadequate social protection, low wage growth, a lack of wage-setting policies, unemployment, and homelessness [ 1 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also food insecurity in developed countries, and, more concretely, among the most vulnerable populations in these countries. Whittle et al (2020) show problems in women with human immunodeficiency virus in the United States, while McKay et al (2020) present the situation in Australia. Moreover, the population with food insecurity in the United States is increasing, particularly among children, according to Belsky et al (2010).…”
Section: Resultsmentioning
confidence: 99%
“…This equates to a larger outlay of money (e.g. $40 extra per month for one 100 g toddler-specific yoghurt daily, and $13 more per month for one 200 mL serve of toddler milk), and with the cost of living increasing and wage growth stagnating [ 31 ], this impacts the household budget, and may become a social equity issue.…”
Section: Discussionmentioning
confidence: 99%
“…Planning a healthy diet takes time [ 20 ] which is in short supply for many families, and they may compromise health for convenience to fit busy lifestyles [ 28 , 30 ]. Food cost is an important determinant of food intake and of food security, with those in lower socioeconomic positions more likely to experience food insecurity [ 31 ] and have dietary patterns that are generally lower in the basic healthy foods such as fresh fruit and veg and higher in discretionary, UP foods [ 32 ]. Dietary intake studies from the US have reported that up to 8% of total dietary intake for toddlers in low-income households comes from added sugars, compared to 2% in higher income households, and the excess sugar, sodium, saturated fat in toddlers’ diets is mostly from commercial foods and drinks [ 33 ].…”
Section: Introductionmentioning
confidence: 99%